The Impact of Intraventricular Hemorrhage and Periventricular Leukomalacia on Mortality and Neurodevelopmental Outcome in Very Preterm and Very Low Birthweight Infants: A Prospective Population-based Cohort Study - Pascal, Aurelie; de Bruyn, Nele; Naulaers, Gunnar; Ortibus, Els; Hanssen, Britta; Oostra, Ann; de Coen, Kris; Sonnaert, Michel; Cloet, Eva; Casaer, Alexandra; D’Haese, James; Laroche, Sabine; et al. (The Journal of pediatrics, 2023)
To survey the incidence of intraventricular hemorrhage (IVH) and periventricular leukomalacia (PVL) by gestational age and to report the impact on mortality and neurodevelopmental outcome in very preterm/very low birthweight infants. This was a population-based cohort study of 1927 very preterm/very low birthweight infants born in 2014-2016 and admitted to Flemish neonatal intensive care units. Infants underwent standard follow-up assessment until 2 years corrected age with the Bayley Scales of Infant and Toddler Development and neurological assessments. No brain lesion was present in 31% of infants born at <26 weeks of gestation and 75.8% in infants born at 29-32 weeks of gestation. The prevalence of low-grade IVH/PVL (grades I and II) was 16.8% and 12.7%, respectively. Low-grade IVH/PVL was not related significantly to an increased likelihood of mortality, motor delay, or cognitive delay, except for PVL grade II, which was associated with a 4-fold increase in developing cerebral palsy (OR, 4.1; 95% CI, 1.2-14.6). High-grade lesions (III-IV) were present in 22.0% of the infants born at <26 weeks of gestational and 3.1% at 29-32 weeks of gestation, and the odds of death were ≥14.0 (IVH: OR, 14.0; 95% CI, 9.0-21.9; PVL: OR, 14.1; 95% CI, 6.6-29.9). PVL grades III-IV showed an increased odds of 17.2 for motor delay and 12.3 for cerebral palsy, but were not found to be associated significantly with cognitive delay (OR, 2.9; 95% CI, 0.5-17.5; P = .24). Both the prevalence and severity of IVH/PVL decreased significantly with advancing gestational age. More than 75% of all infants with low grades of IVH/PVL showed normal motor and cognitive outcome at 2 years corrected age. High-grade PVL/IVH has become less common and is associated with adverse outcomes.